Ministry Of Housing, Utilities And Urban Communities Decree No. 439 Of The Year 2022 Amending Certain Provisions Of Decree No. 1 Of The Year 1993 And Amendments Thereof - Ended By Ministerial Decree No. 299 Of The Year 2019 - On Approving The Rules Of Registration, Classification And Order Of The Contractors In The Egyptian Federation For Construction And Building Contractors = وزارة الإٍسكان والمرافق والمجتمعات العمرانية قرار رقم 439 لسنة 2022 بتعديل بعض أحكام القرار الوزارى رقم 1 لسنة 1993 وتعديلاته والمنتهية بالقرار الوزارى رقم 299 لسنة 2019 باعتماد قيد وتصنيف وترتيب أعضاء الاتحاد المصرى لمقاولى التشييد والبناء - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic